Design of Energy Harvesting Circuit for Low Power Application - Dixit, Nitesh Kumar; Rangra, Kamal J.; Sharma, Y. C. (Asian Journal of Electrical Sciences, 2018)
Piezoelectric energy harvesting is the technology to convert wasted vibration energy to an electrical energy output. A considerable amount of energy is dissipated in PEH to flip the output voltage through the internal capacitor and resistor of piezoelectric (PZT) material. One of the most effective techniques to harvest this power loss is called Synchronized Switch Harvesting on Inductor (SSHI) technique. Parallel SSHI technique has been used to flip the terminal voltage of the PEH through external inductor. A new simple and effective self-powered circuit has been introduced in this paper for this purpose. The new circuit uses two capacitors only to detect the flipping points of terminal voltage and enhance the power output